2004
DOI: 10.1007/s11894-004-0042-1
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of cholesterol gallstone formation: Searching for Lith (gallstone) genes

Abstract: The genetics of cholesterol cholelithiasis is complex because a number of interacting genes regulate biliary cholesterol homeostasis. Quantitative trait locus (QTL) analysis is a powerful method for identifying primary rate-limiting genetic defects and discriminating them from secondary downstream lithogenic effects caused by mutations of the primary genes. The subsequent positional cloning of such genes responsible for QTLs may lead to the discovery of pathophysiologic functions of Lith (gallstone) genes. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
53
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(55 citation statements)
references
References 87 publications
2
53
0
Order By: Relevance
“…However, lack of a significant change in hepatic SHP content between genotypes argues against involvement of SHP-dependent pathways in CYP7A1 repression. 4 Alternately, PKC␤ directly phosphorylates nuclear receptors (LXR, FXR, and PPAR␣) and/or the transcription factor SREBP-1c and suppresses CYP7A1 transcription, which is in line with earlier reports showing the ability of PKCs to phosphorylate and modify the above transcription factors (59 -63). The absence of changes in LXR (ABCG5/8) or FXR (ABCB11) target genes argues against a mechanism involving these transcriptional regulators.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…However, lack of a significant change in hepatic SHP content between genotypes argues against involvement of SHP-dependent pathways in CYP7A1 repression. 4 Alternately, PKC␤ directly phosphorylates nuclear receptors (LXR, FXR, and PPAR␣) and/or the transcription factor SREBP-1c and suppresses CYP7A1 transcription, which is in line with earlier reports showing the ability of PKCs to phosphorylate and modify the above transcription factors (59 -63). The absence of changes in LXR (ABCG5/8) or FXR (ABCB11) target genes argues against a mechanism involving these transcriptional regulators.…”
Section: Discussionsupporting
confidence: 88%
“…Approximately 12% of individuals in the United States are affected by gallstones with more than 750,000 cholecystectomies being performed each year (1,2). The pathogenesis of gallstone disease is multifactorial, involving interactions between genetic and environmental factors that result in bile supersaturation, gallbladder hypomotility, and precipitation/nucleation of cholesterol microcrystals (3,4). Obesity, aging, estrogen treatment, and diabetes are consistently associated with a higher risk of gallstones (5,6).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…On chow, the APO-B100 deficiency in S tudies in humans and inbred mice have demonstrated that a complex genetic basis determines the individual and strain predisposition to develop cholesterol gallstones in response to environmental factors. 1 The primary pathophysiological defect involved in cholesterol gallstone formation is increased biliary secretion of cholesterol from the liver, which produces bile supersaturated with cholesterol. 2 Subsequently, biliary cholesterol precipitates as "anhydrous" and monohydrate crystals, which grow and agglomerate toward the formation of macroscopic stones in the gallbladder.…”
mentioning
confidence: 99%
“…1 The primary pathophysiological defect involved in cholesterol gallstone formation is increased biliary secretion of cholesterol from the liver, which produces bile supersaturated with cholesterol. 2 Subsequently, biliary cholesterol precipitates as "anhydrous" and monohydrate crystals, which grow and agglomerate toward the formation of macroscopic stones in the gallbladder.…”
mentioning
confidence: 99%